EVALUATION OF ONLINE SINGLE SUBMISSION SERVICES OF THE INVESTMENT OFFICE AND ONE-STOP INTEGRATED SERVICES IN BANTAENG REGENCY - Sulfira, Sulfira; Yamin, Muh Nur; Sakawati, Herlina (Universitas Negeri Makassar, 2025)
This research aims to determine the evaluation of the Online Single Submission Service for the Investment Service and One Stop Integrated Services in Bantaeng Regency, using a qualitative approach and producing descriptive data. Data collection uses observation, interview and documentation techniques. The results of the research show that the Evaluation of the Online Single Submission Service for the Investment Service and One Stop Integrated Services in Bantaeng Regency has gone well. This shows that the Investment Service's Online Single Submission Service and One Stop Integrated Services in Bantaeng Regency provides many benefits. Adequate facilities and infrastructure make the Online Single Submission Service process easier for the Investment Service and One Stop Integrated Services in Bantaeng Regency. All people living in Bantaeng Regency can apply for a permit without any fees. Officers implementing the Online Single Submission Service show a good attitude in serving applicants. The existence of this Online Single Submission Service is very useful for the welfare of society